2009
DOI: 10.1073/pnas.0907163107
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification and marine trace gas emissions

Abstract: The oceanic uptake of man-made CO 2 emissions is resulting in a measureable decrease in the pH of the surface oceans, a process which is predicted to have severe consequences for marine biological and biogeochemical processes [Caldeira K, Wickett ME (2003) Nature 425:365; The Royal Society (2005) Policy Document 12 /05 (Royal Society, London)]. Here, we describe results showing how a doubling of current atmospheric CO 2 affects the production of a suite of atmospherically important marine trace gases. Two CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
126
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(153 citation statements)
references
References 37 publications
23
126
4
Order By: Relevance
“…The phytoplankton populations in both treatments were dominated numerically by picoeukaryotes, whereas cryptophytes, prymnesiophytes (including coccolithophores) and other flagellates of uncertain taxonomic affiliations made the greatest contributions to phytoplankton biomass (Hopkins et al, 2010). Although not identified taxonomically, two size classes of picoeukaryotes ('small' and 'large') were present.…”
Section: Impact Of Ocean Acidification On Picoeukaryotesmentioning
confidence: 95%
See 3 more Smart Citations
“…The phytoplankton populations in both treatments were dominated numerically by picoeukaryotes, whereas cryptophytes, prymnesiophytes (including coccolithophores) and other flagellates of uncertain taxonomic affiliations made the greatest contributions to phytoplankton biomass (Hopkins et al, 2010). Although not identified taxonomically, two size classes of picoeukaryotes ('small' and 'large') were present.…”
Section: Impact Of Ocean Acidification On Picoeukaryotesmentioning
confidence: 95%
“…Biological sampling was initiated the next day (day 0), following the addition of nutrients to stimulate phytoplankton growth to final concentrations of 17 mmol l À1 NO 3 À and 1.0 mmol l À1 PO 4 2À (Hopkins et al, 2010). Throughout the experiment, the enclosure covers were only removed for sampling and the headspaces were flushed with air (ambient conditions) or CO 2 -enriched air (750 ppmV, acidified treatment) to help maintain pH.…”
Section: Experimental Background and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Hopkins et al (2010) found decreased production of dimethylsulphide and volatile iodocarbon compounds under high pCO 2 conditions.…”
Section: Trace Gas Productionmentioning
confidence: 99%